TINJAUAN TENTANG PEMENUHAN HAK DEBITUR DALAM PERJANJIAN JAMINAN FIDUSIA OLEH PT. PEGADAIAN (PERSERO) CABANG PASAR KODIM PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Fiduciary Guarantee is a security right on movable objects, both tangible and intangible and immovable objects, especially buildings that cannot be encumbered with Mortgage Rights as referred to in Law Number 4 of 1996 concerning Mortgage Rights which remain in the control of the fiduciary giver, as collateral. for the repayment of debt in the micro business credit agreement by the debtor.The main problem in this study is how to fulfill the debtor's rights in the fiduciary guarantee agreement by PT. Pegadaian (Persero) Pekanbaru Kodim Market Branch and what are the legal consequences of not fulfilling the debtor's rights in the fiduciary guarantee agreement by PT. Pegadaian (Persero) Pekanbaru Kodim Market Branch.The research method used is Sociological Legal Research, namely interviews and questionnaires as a data collection tool. In this study, the authors conducted direct research at the research site to obtain materials, data and information related to this research. The nature of the research, this research is descriptive, which provides a clear and detailed description of an event that occurred.Based on the results of the study, it is known that, the fulfillment of the debtor's rights in the fiduciary guarantee agreement is the right to control the object that is used as the object of collateral, because the object of the guarantee is a supporter of the business continuity of the fiduciary provider (Article 1 paragraph (1) UUJF). If the object of the guarantee is executed, the fiduciary giver has the right to receive the remainder of the proceeds from the sale of the object that is the object of the fiduciary guarantee after deducting the payment for the settlement of his debts (Article 34 paragraph (1) UUJF). On the other hand, the fiduciary giver is obliged to maintain and maintain the safety of the object that is the object of the fiduciary guarantee. Mandatory to provide a report on the condition of the object that is the object of the guarantee. If the object that is the object of the guarantee is executed, then the fiduciary giver is obliged to surrender the object (Article 30 UUJF). And they are obliged to pay their debts until they are paid off, especially from the proceeds from the sale of the fiduciary collateral, if the fiduciary provider defaults (Article 34 paragraph (2) UUJF). And the obstacles to fulfilling the debtor's rights in the fiduciary guarantee agreement by PT. Pegadaian (Persero) Pasar Kodim Pekanbaru Branch, namely the case that occurred was one of the civil cases that did not make a deed of imposition of fiduciary guarantees and the obligation to register fiduciary guarantees and were not in accordance with the procedural mechanisms that had been determined by the provisions of the legislation. Fiduciary guarantees that are not registered with a fiduciary institution will be constrained in terms of executing the object of the guarantee, because they do not have a strong legal standing, namely in this case they do not have a fiduciary deed or certificate.